Relationship between Age, Pregnancy Distance, Anc Visits with the Incidence of Anemia in Pregnant Women at Health Center 4 Ulu, Seberang Ulu District 1 Palembang City in 2021 - Melanda; Yulizar; Satra Yunola (Institute of Computer Science (IOCS), 2022)
Anemia in pregnancy is a decrease in hemoglobin levels that occurs during pregnancy due to iron deficiency or folate deficiency. The prevalence of anemia in Indonesia in pregnant women according to the SKRT is still quite high, namely 40.1%. Factors that can cause anemia in pregnancy include age, gestational distance, parity, education level, economic status, knowledge, attitude, food intake, ANC visits and adherence to Fe tablet consumption. The purpose of this study was to determine the relationship between age, gestational age, ANC visits simultaneously with the incidence of anemia in pregnant women at Puskesmas 4 Ulu, Seberang Ulu 1 District, Palembang City in 2021. The research design used in this study was an analytic survey with a cross sectional design. . The population in this study was the sample in this study as many as 70 pregnant women who did a pregnancy check at the 4 Ulu Health Center, Seberang Ulu 1 District, Palembang City until December 2021. Based on the results of research using the chi-square statistical test, it was found that there was a significant relationship between age and the incidence of anemia in pregnant women obtained p. value = 0.001, there is a significant relationship between the distance of pregnancy with the incidence of anemia in pregnant women, obtained p. value = 0.001, there is a significant relationship between ANC visits and the incidence of anemia in pregnant women, obtained p. value = 0.000, it can be concluded that there is a significant relationship between age, gestational distance and ANC visits with the incidence of anemia in pregnant women.